PENGARUH DIKLAT DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA SATUAN POLISI PAMONG PRAJA KABUPATEN BREBES - Amsirun amsirun (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
This study takes the title Influence of Training and Leadership on Employee Performance in the Civil Service Police Unit of Brebes Regency. The formulation of the proposed problem is whether there is an effect of training and leadership on the performance of SATPOL PP members in Brebes Regency, how much influence is the training and leadership simultaneously on the performance of SATPOL PP members in Brebes Regency and whether the influence of education and leadership influence significantly on the performance of SATPOL PP members in Brebes Regency. The hypothesis proposed is that there is an influence between training and leadership on the performance of SATPOL PP members in Brebes Regency, there is a large influence between training and leadership on the performance of SATPOL PP members in Brebes Regency and there is a significant influence between education and leadership on the performance of SATPOL PP members in Brebes Regency. Based on the results of the research, it can be said that the Spearman rank correlation between training and performance is 0.685. Which has a correlation meaning between training and performance is strong. While the Spearman rank correlation between leadership and performance obtained a value of 0.741. Which means that the correlation between leadership and performance is strong. While the t-test using a 95 percent confidence level (α / 2 = 0.05 / 2 = 0.025) and the degree of freedom Nk (51-2) obtained t table of 2.011 and the calculation results in SPSS shows X1 = 3.803 which means that t count> t table . This shows that Ho was refused or training significantly affected the performance of the Civil Service Police Unit of Brebes Regency. Whereas in X2 obtained 4.620 which means that t count> t table. This shows that Ho is rejected or leadership significantly influences the performance of the Civil Service Police Unit of Brebes Regency. The results of these calculations concluded that partially the training and leadership variables have a significant influence on the performance variables.